Strategy formulation for kanawa coffee to win the competition using diamond strategy framework - Ikhsan Jauhari, Mochamad; Toha, Mohamad (The Indonesian Journal of Business Administration, 2016)
ABSTRACT - Food and beverages business is one of the business that have a promising future because food and beverages is a primary need for people. Kanawa Coffee is a coffee shop located in Suryo street, south Jakarta which is a mainstream area for find a restaurant or coffee shop. There are many competitors in the industry that made the competition in this industry so tight, so Kanawa Coffee need to have a good strategy to win the competition also avoid the chances of imitation.The research was conducted with scanning the internal and external environment of the business and also through the data collection from interview and questionnaire. The strategy formulation method that will be used is Diamond Strategy, strategies that has been formulated will be made into a layered activity mapping to avoid the chances of imitation and also made into a new business model canvas for Kanawa Coffee. Kanawa Coffee should improve the key variables that influenced people, So the strategies that has been formulated are based on the key variables itself. There is a chance for competitor to imitate the strategy that has been proposed, so to avoid the chances of imitation Kanawa Coffee should do layered activities in order to make competitor difficult to imitate the strategies. With the result of diamond strategy formulation and strategy to avoid imitation, there are an improvement in business model canvas of Kanawa Coffee. Management and staffs of Kanawa Coffee need to be prepared before execute the strategies proposed and then do the improvement as soon as possible. The improvement need to be measured by Kanawa Coffee in order to know the impact of each strategy. In order to implement the strategy successfully Kanawa Coffee need to maintain their relationship with their stakeholder because it also became the key for Kanawa Coffee to implement the strategies successfully and win the competition in the future.Â Keywords: Business Strategy, Coffee shop business, Diamond Strategy , Attack Strategy, Business Model CanvasÂ